Variations in power performance and perceptual responses to training in Olympic boxers over a 7-month training period - Pereira, L. A.; Romano, F.; Alves, M.; Mercer, V. P.; Bishop, C.; Franchini, E.; Loturco, I. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To assess the variations in power performance and perceptual training responses and compare the physical performance of national boxing athletes qualified or not qualified for the Tokyo Olympic Games over a 7-month training period. Methods: Twelve amateur boxers from the Brazilian national team were tested 6 times across 7 months. In the first assessment, boxers performed squat and countermovement jumps and bench press, prone bench pull, half squat, and jump squat power tests. In the following testing sessions, only countermovement jump and bench press power were assessed. In addition, the rating of perceived exertion and total quality recovery status were assessed in 106 training sessions across the study. Independent t test and repeated-measures analysis of variance were used for data analysis purposes. Results: No significant differences (P > .05) were observed between Olympic and non-Olympic groups for any test variables (effect size [95% CI] ranging from 0.01 [-1.13 to 1.13] to 0.69 [-0.53 to 1.79]). No significant changes (P > .05) were detected throughout the study for countermovement jump height and bench press power in either group (effect size [95% CI] ranging from 0.01 [-1.13 to 1.13] to 1.03 [-0.25 to 2.14]). Overall, both groups exhibited similar variations in both rating of perceived exertion and total quality recovery over the 7-month period. Conclusions: Within the same national team, power-related performance was similar between Olympic and non-Olympic boxers. The maintenance of power abilities and optimization of technical and tactical skills seem to be key issues to consider during the final stages of preparation for international boxing competitions.